Educação ambiental em uma escola municipal de Pato Branco Pr: uso e ocupação do solo em uma bacia hidrográfica urbana - Alves, Marcos Henrique Carneiro (2022)
The impacts to the environment resulting from the search for effective means of development molded in a capitalist model, causing complications to the quality of life of people in society. The natural resource extraction of the planet's, substantiate on the false conception of its infinity, solvable a major contributor to the environmental problems that configure the current global scenario. This said, urban development, for example, when in a disorderly adjested, way can complications couse, as problems in the maintenance of water resources, socio-spatial cleavage, privation of opportunities, poverty, misery and mainly aggravating aresing to the use, occupation and waterproofing of the soil, which can result in disasters putting human life at risk. Given context, Environmental Education actions and projects that seek to awaken a critical view of the local reality can exerccise an important role in the construction of socioenvironmental thinking. However, there is a need for these actions to enable the pay-in of diverse types of knowledge, unlike actions that work on hematic in isolation, which are not part of the daily lives of their participants, losing potential for reflection. In view of this, the presente study is an action of Critical Environmental Education that, through Education in Soils, to promote the capacitation of teachers in related matters the use and occupation of land in urban river basins, in a municipal school in the city of Pato Branco – PR. The local reality of an accelerated urban development process. In intention to achieve the proposed objective, the present stady subdivided its methodological application in four phases: Phase a) Application of the semistructured questionaire I; Phase b) Presentation of the elaborated contents; Phase c) Elaboration of EAS scripts: materials for use in classroom; Phase d) Application of the semistructured questionnaire II. Both phases have to scope integrate the environmental relations between Urban Development, Soil conservation, Use and Occupancy in Urban river basins. By its investigative characteristic in relation to the interaction between human and nature, the present stady has a qualitative character, but it also fits into the molds of action stady, so pormote a joint action with teachers of the School Municipal José Fraron. Of eighteen teachers who have exclusive dedication in the municipal school, only three participated in the stady, however, through the application of a script of Environmental Education In Solo, the participating teachers convey on the knowledge acquired during the phase of "Presentation of the elaborated contents" for their students and not only reinforced the subject they had seen, but also play-in the roles of auxiliary agents in the construction of socioenvironmental thinking.